Cannabis Use Is Differentially Associated with Individual Facets of Impulsivity through Expectancy Effects: A Comprehensive Application of the Acquired Preparedness Model. Issue 4 (8th August 2021) - Falco, Caitlin A.; De Young, Kyle P.; Livingston, Nicholas R.; Kilwein, Tess M.; Looby, Alison
ABSTRACT: The acquired preparedness model (APM) posits that the relationship between impulsivity and substance use is mediated by drug effect expectancies. Though the APM has been utilized to explain college student cannabis use, a comprehensive model conceptualizing impulsivity as a multidimensional construct has not been examined. Guided by the APM, the current study examined facets of impulsivity as simultaneous predictors of cannabis use through positive and negative expectancies. College students ( N = 478) completed an online survey assessing frequency of past-month cannabis use, facets of impulsivity, and cannabis expectancies. Using a bootstrapped path analysis, five facets of impulsivity were modeled as predictors of past-month cannabis use via positive and negative expectancies. A zero-inflated Poisson distribution was used, wherein dichotomous past-month cannabis use was examined independently of frequency. There was a significant indirect effect of sensation seeking on both increased likelihood and frequency of use through strong positive expectancies. Additionally, both negative and positive urgency were associated with a decreased likelihood of use through stronger negative expectancies, while lack of premeditation was associated with an increased likelihood of use through weaker negative expectancies. These results underscore the importance of examining impulsivity as a multi-dimensional construct in the understanding of college student cannabis use behavior.